Revitalisasi Budaya Di Era Digital Dan Eksplorasi Dampak Media Sosial Terhadap Dinamika Sosial-Budaya Di Tengah Masyarakat - Agustinus Gulo (Pusat Riset dan Inovasi Nasional, 2023)
In terms of research methodology, this study uses a qualitative approach to explore the phenomenon of cultural revitalization in the digital era and explore the impact of social media on socio-cultural dynamics. An in-depth analysis of various literatures and social media content was conducted to understand the context and complexity of the phenomenon. The results of the exploration show that social media not only plays a role in changing the way people interact, but also provides a platform for political participation, activism, and creative economic development. Its implications for socio-cultural dynamics are complex, requiring multidisciplinary thinking from the perspectives of sociology, anthropology, psychology, economics, and socio-cultural political science. In addition, digital revitalization must reflect the inclusiveness of technological access to ensure the sustainability of this digital revolution does not leave some communities behind. In conclusion, the exploration of the impact of social media in society is a deep and complex study, requiring a holistic understanding to direct digital cultural revitalization towards positive and sustainable development. Cultural revitalization in the digital era and the exploration of the impact of social media on socio-cultural dynamics in society are the main focus of this study. The phenomenon of digital cultural revitalization reflects a significant shift in the way society uses, creates and understands an increasingly relevant culture. Social media, as a major element in digital culture, plays a central role in changing the socio-cultural dynamics of society. Exploring the impact of social media is essential to understanding how these changes permeate people's daily lives, shape socio-cultural frameworks, and influence global interactions.